Rising Temperatures Advance Start and End of the Breeding Season of an Alpine Bird - Carole A. Niffenegger; Sabine M. Hille; Christian Schano; Fränzi Korner‐Nievergelt (Ecology and Evolution)
ABSTRACT Many bird species have advanced the start of the breeding season as a response to climate change. The duration of the breeding season and how it is affected by climate change are far less studied but are important for the re‐nesting potential. Re‐nesting includes both the replacement of a failed breeding attempt or breeding successfully multiple times within one season and can therefore impact fitness. Some species profit from an earlier start of breeding through a higher re‐nesting potential, whereas other species also advance the end of breeding season as conditions for breeding deteriorate. Here, we explored how temperature, precipitation, and snow conditions influence the start, end, and duration of the breeding season of a cold‐adapted high‐elevation songbird. We fitted generalized additive models with more than 12,000 citizen science observations of white‐winged snowfinches (Montifringilla nivalis) to estimate breeding phenology between 2006 and 2021. Our results indicate that higher prebreeding temperatures and reduced April precipitation were associated with an earlier start of breeding. However, later during the breeding season higher temperatures shortened the breeding season through an earlier end of the breeding season. Despite adjusting the timing of reproduction to prevailing environmental conditions, average temperatures during the breeding season increased over the 16‐year study period. Therefore, snowfinches need to move to higher elevations in order to track the thermal conditions. This study highlights the complex relationship between phenology and environmental conditions and illustrates how much the breeding conditions are currently changing for high‐elevation species.